Cytochrome P450 enzymes activity in rat liver under conditions of toxic injury and partial hepatectomy - Н. P. Kopylchuk; I. M. Nykolaichuk; М. S. Ursatyi (The Ukrainian Biochemical Journal, 2025)
The unique liver ability for reparative regeneration plays a decisive role in restoring its homeostatic potential. However, in certain clinical situations, in particular, due to the damage caused by toxicants of a medicinal origin, the regenerative response may be impaired. Uncontrolled use of nonsteroidal anti-inflammatory drug paracetamol (acetaminophen, APAP) is among the leading causes of acute liver failure. The study focuses on evaluating of p-hydroxylase, N-demethylase, N-oxygenase activity of cytochrome P450 (CYP) enzymes as well as the CYP content in the microsomal fraction of the liver of rats subjected to partial hepatectomy following acute acetaminophen-induced toxic injury. White non-linear rats were divided into two groups: with partial hepatectomy (resection of 2/3 of liver tissue) and with partial hepatectomy following oral acetaminophen administration for 2 days at a dose of 1250 mg/kg b. w. Experimental data were obtained at 0 (control), 24, 48, 72 and 168 h after hepatectomy. The regeneration process at the early stages after partial hepatectomy in animals that were not exposed to APAP injury was accompanied by the suppression of aniline p-hydroxylase and dimethylaniline N-demethylase activity, along with a simultaneous decrease in cytochrome P450 content against the background of a compensatory increase of N-oxygenase activity. Liver tissue recovery after partial hepatectomy in animals with APAP injury was characterized by an increase in cytochrome P450 content along with concurrent activation of aromatic hydroxylation, N-dealkylation, and N-oxidation reactions throughout the entire regenerative period. The data obtained indicate the initiating of competing pathways of acetaminophen detoxification and/or toxification at different time intervals during the process of liver reparative regeneration.